TRPM4 and TRPM5 are both required for normal signaling in taste receptor cells - Banik, Debarghya Dutta; Freichel, Marc (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Peripheral taste receptor cells use multiple signaling pathways to transduce taste stimuli into output signals that are sent to the brain. Transient receptor potential melastatin 5 (TRPM5), a sodium-selective TRP channel, functions as a common downstream component in sweet, bitter, and umami signaling pathways. In the absence of TRPM5, mice have a reduced, but not abolished, ability to detect stimuli, suggesting that a TRPM5-independent pathway also contributes to these signals. Here, we identify a critical role for the sodium-selective TRP channel TRPM4 in taste transduction. Using live cell imaging and behavioral studies in KO mice, we show that TRPM4 and TRPM5 are both involved in taste-evoked signaling. Loss of either channel significantly impairs taste, and loss of both channels completely abolishes the ability to detect bitter, sweet, or umami stimuli. Thus, both TRPM4 and TRPM5 are required for transduction of taste stimuli.